Multi-Objective Optimization of Multi-Energy Flow Coupling System With Carbon Emission Target Oriented - Zong, Xuanjun; Yuan, Yue; Wu, Han (Frontiers in Energy Research, 2022)
In this paper, aiming to achieve the target of carbon emission orientation, a multi-objective optimization model of multi-energy flow coupling system is proposed, in which all the environmental protection, system economy and energy efficiency are comprehensively considered as the addressed objectives. To solve the developed model, by combining the analytic hierarchy process (AHP) and the improved entropy weight method, a so-called AHP-improved entropy weight method is proposed and utilized for weighting the considered objectives, and the model is transformed into a single objective optimization problem, namely the collaborative optimization model. Then, to expedite the process, a simplified primal dual interior point method is proposed to solve the model. Finally, the results of a case study indicate that the proposed multi-objective collaborative optimization can obtain the optimal solution of the system. In addition, the convergence and global optimization ability of the simplified primal dual interior point method show better characteristics when solving the proposed model.